Zambia Economic Brief, June 2014 : Promoting Trade and Competitiveness - What Can Zambia Do? - World Bank Group (World Bank, Washington, DC, 2014)
Zambia continues to experience strong growth, but challenges are building up. Copper prices are declining, and global financial conditions are tightening. At home, the fiscal deficit is becoming difficult to manage, and Zambia's currency has sharply depreciated. The government intends to reduce future budget deficits, but this would involve making difficult political choices. In the past few years inflation and interest rates have declined and the currency has been relatively stable, providing an environment for growth and reducing poverty. High inflation would hurt the poor most. The brief specifically focuses on the opportunity for Zambia to emerge as a major food exporter to Eastern and Southern Africa and the policy direction that would take it there; the need to reduce high costs of crossing borders that will facilitate regional trade in non-copper products; and a long-term approach to developing competitiveness of the local mining supply cluster.